Fish canning wastewater treatment by activated sludge: Application of factorial design optimization - Raquel O. Cristóvão (2015)
The optimization of hydraulic retention time (HRT) and initial organic matter concentration for dissolved organic carbon (DOC) abatement of wastewater from a fish canning industry of northern Portugal by activated sludge was investigated using response surface methodology (RSM). The two parameters were chosen since it was found that the treatment efficiency is mainly influenced by them. The experimental data on DOC removal were fitted into a quadratic polynomial model using factorial design and RSM. The optimum process conditions were determined by analyzing the response surface of a three-dimensional plot and by solving the regression model equation. The obtained results showed a HRT of 6.4. h and an initial DOC of 406.2. mg/L as the best treatment conditions. Under these conditions, the maximum predicted DOC removal was 88.0%, confirming the feasibility and the reliability of fish canning wastewater treatment by activated sludge for organic content removal. (c) 2015 The Authors.